2018
DOI: 10.1038/s41598-018-22567-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature, moisture, and metal salt content on dielectric properties of rice bran associated with radio frequency heating

Abstract: Dielectric heating including microwave (MW) and radio frequency (RF) energy has been regarded as alternative thermal treatments for food processing. To develop effective rice bran (RB) stabilization treatments based on RF and MW heating, dielectric properties (DPs) with dielectric constant (ε′) and loss factor (ε″) of RB samples at frequencies (10–3000 MHz), temperatures (25–100 °C), moisture content (MC, 10.36–24.69% w.b.) and three metal salt levels (0.05–2.00%) were determined by an open-ended coaxial probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 35 publications
(37 reference statements)
2
6
0
Order By: Relevance
“…On the other hand, enhancement in the HARF exposure period (more than 15 min) showed undesirable changes in nutritional attributes of pearl millet. In recent studies, similar trends were also established for RF-treated rice bran (Liao et al, 2020;Ling, Liu, et al, 2018;Ling Lyng et al, 2018a); and wheat germ (Ling et al, 2018b(Ling et al, , 2020.…”
Section: Physicochemical Characteristics Of Pearl Milletsupporting
confidence: 68%
“…On the other hand, enhancement in the HARF exposure period (more than 15 min) showed undesirable changes in nutritional attributes of pearl millet. In recent studies, similar trends were also established for RF-treated rice bran (Liao et al, 2020;Ling, Liu, et al, 2018;Ling Lyng et al, 2018a); and wheat germ (Ling et al, 2018b(Ling et al, , 2020.…”
Section: Physicochemical Characteristics Of Pearl Milletsupporting
confidence: 68%
“…Extrusion treatment was observed to be an effective method for corn germ stabilization, and extrusion temperature plays a more important role. As is shown in Table . 3 and Figure 5, the effect of extrusion temperature on FFA content is almost consistent with the change of LA activity, and the LA and LOX in corn germ could catalyze the degradation and oxidation of fat components and produce FFA, resulting in the accumulation of aldehydes, which further affects the smell and quality of corn germ (Ling et al, 2018). The shelf lives of extruded corn germ were predicted according to different storage temperatures in 50% relative humidity.…”
Section: Storage Experimentssupporting
confidence: 62%
“…Ramezanzadeh et al [ 46 ] also reported higher moisture content in the SRB initially than in the NSRB samples. The addition of water to the samples increases the ionic conductivity, contributing to faster electromagnetic energy absorption and a higher heating rate [ 47 ]. Although the moisture increment might lead to an inefficient inactivation of lipoxygenase, Ramezanzadeh et al [ 46 ] found that its activity decreased due to the lack of FFA, the substrate for lipoxygenase activity.…”
Section: Resultsmentioning
confidence: 99%